2002
DOI: 10.1177/014616702237651
|View full text |Cite
|
Sign up to set email alerts
|

Ease of Retrieval Effects in Persuasion: A Self-Validation Analysis

Abstract: Three studies are reported examining a new explanation for ease of retrieval effects in persuasion. In each study, participants read a persuasive communication and were induced to generate either a low or high number of favorable or unfavorable thoughts in response. In conflict with the assumptions of most previous studies, the authors predicted and found that ease of retrieval effects occur primarily under high rather than low-elaboration conditions. Under high-elaboration conditions, people were more influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
205
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(225 citation statements)
references
References 33 publications
14
205
1
5
Order By: Relevance
“…Although this correspondence in findings is conceptually sound due to the functional similarities of processing motivation and processing capacity (e.g., Chen & Chaiken, 1999;Petty & Cacioppo, 1986;Fiske & Neuberg, 1990;Fazio & Towles-Schwen, 1999), one may reasonably ask how the present findings relate to other prior research endeavors that showed the reverse effect: Reliance on accessibility experiences in conditions of high but not low processing motivation (Wänke & Bless, 2000;Tormala et al, 2002). We think that both a methodological and conceptual explanation may account for this (seeming) inconsistency.…”
Section: Theoretical Implicationsmentioning
confidence: 57%
See 3 more Smart Citations
“…Although this correspondence in findings is conceptually sound due to the functional similarities of processing motivation and processing capacity (e.g., Chen & Chaiken, 1999;Petty & Cacioppo, 1986;Fiske & Neuberg, 1990;Fazio & Towles-Schwen, 1999), one may reasonably ask how the present findings relate to other prior research endeavors that showed the reverse effect: Reliance on accessibility experiences in conditions of high but not low processing motivation (Wänke & Bless, 2000;Tormala et al, 2002). We think that both a methodological and conceptual explanation may account for this (seeming) inconsistency.…”
Section: Theoretical Implicationsmentioning
confidence: 57%
“…We started out from the observation that despite the prominence of the ease-of-retrieval heuristic, little empirical evidence is available regarding factors that moderate individuals' reliance on their retrieval experiences (for exceptions, Rothman & Schwarz, 1998;Dijksterhuis et al, 1999;Tormala et al, 2002;Ruder & Bless, 2003). In particular, we were not aware of any evidence on the potential role of processing capacity as a moderator of the use of accessibility experiences in judgment formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, there is growing evidence that subjectively experienced effort is only one of many variables that can influence judgments in the ''ease-of-retrieval paradigm''. Thus, literature shows that judgment effects in this paradigm are influenced by variables such as imagined effort (Wänke et al 1997), the difference between expected and experienced effort (Raghubir and Menon 2005;Hansen and Wänke in press), or confidence in the information conveyed by one's own thoughts (Tormala et al 2002). Examining the role of these variables may help understand why the mediation from the manipulation to the judgment effects via subjective effort was not significant in the full mediation model.…”
Section: Discussionmentioning
confidence: 93%